2013
DOI: 10.4103/1817-1737.105710
|View full text |Cite
|
Sign up to set email alerts
|

Saudi regulations for the accreditation of sleep medicine physicians and technologists

Abstract: The professional content of sleep medicine has grown significantly over the past few decades, warranting the recognition of sleep medicine as an independent specialty. Because the practice of sleep medicine has expanded in Saudi Arabia over the past few years, a national regulation system to license and ascertain the competence of sleep medicine physicians and technologists has become essential. Recently, the Saudi Commission for Health Specialties formed the National Committee for the Accreditation of Sleep M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…[26][27][28] To ascertain the quality of medical care provided to patients with sleep disorders, the institution of national regulations and policies is essential to verify the competency of practicing sleep medicine physicians and technologists. The licensing of sleep medicine practitioners and technicians implies that the local health authorities recognize sleep medicine as a distinct medical specialty.…”
Section: Sleep M Edi Ci Ne and Technology Accreditati Onmentioning
confidence: 99%
See 2 more Smart Citations
“…[26][27][28] To ascertain the quality of medical care provided to patients with sleep disorders, the institution of national regulations and policies is essential to verify the competency of practicing sleep medicine physicians and technologists. The licensing of sleep medicine practitioners and technicians implies that the local health authorities recognize sleep medicine as a distinct medical specialty.…”
Section: Sleep M Edi Ci Ne and Technology Accreditati Onmentioning
confidence: 99%
“…Therefore, the Saudi Commission for Health Specialties (SCHS) formed the National Committee for the Accreditation of Sleep Medicine Practice, which developed national accreditation criteria for physicians and technologists in 2012. 26 The accreditation guidelines considered the diversity of training programs previously available to current sleep medicine physicians. The guidelines define a sleep medicine physician as a medical doctor (MD) who is trained in the subspecialty of sleep medicine and has competence in the clinical assessment, physiological testing, diagnosis, management, and prevention of sleep and circadian rhythm disorders.…”
Section: Sleep M Edi Ci Ne and Technology Accreditati Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of those studies were conducted several years ago. For example, an earlier study conducted in Saudi Arabia (1999)6 revealed that only 40% of physicians identified the link between OSA and ischemic heart disease, 43% did not realize that sleep medicine was a distinct specialty and 85% had never attended a lecture on sleep medicine.Since then, the awareness of sleep medicine and sleep disorders has increased, the service has expanded, new sleep disorder centers have been opened, many specialists have joined the field, the Saudi Commission for Health Specialties has recognized sleep medicine as an independent specialty and subspecialty training programs have been established in the country 1,2. Therefore, we designed this study to assess PCPs’ attitudes and knowledge toward sleep and sleep disorders in Saudi Arabia using standardized validated questionnaires and to compare the new findings with the 1999 survey 6…”
mentioning
confidence: 99%
“…To date, several procedures have been developed to perform the certification process. In some countries, for instance, the USA [1][2][3], sleep medicine is considered an independent medical subspecialty, and in Germany [4,5] and Saudi Arabia [6], its status as a subspecialty has been officially acknowledged. In other countries, expertise is certified by scientific societies or academic institutions.…”
Section: Sleep Medicine Certification For Physicians In Spainmentioning
confidence: 99%